Reconstruction of Lateral Skull Base Defects: A Comparison of the Submental Flap to Free and Regional Flaps. (15th March 2016) - Howard, Brittany E.; Nagel, Thomas H.; Barrs, David M.; Donald, Carrlene B.; Hayden, Richard E.
Abstract : Objectives: To compare reconstructive techniques, operative times, duration of hospitalization, and need for subsequent flap revisions between reconstructive approaches to lateral skull base defects. Study Design: Case series with chart review. Setting: Tertiary academic referral center. Subjects: Patients (n = 31) undergoing reconstruction of composite lateral skull base defects from 2002 to 2014. Methods: Data were analyzed for demographics, tumor characteristics, reconstructive technique, operative time, duration of hospitalization, complications, and outcomes. Results: Thirty‐one patients were identified for inclusion. Lateral temporal bone defects resulted from resection of malignant lesions, including squamous cell carcinoma (n = 25), basal cell carcinoma (n = 2), and other carcinoma (n = 4). Defects were reconstructed with submental flaps (n = 16), pedicled latissimus dorsi flaps (n = 6), and free anterolateral thigh flaps (n = 9). All cases involved neurosurgery, neurotology, and head and neck surgery services. Although time of surgical resection was similar, time saving was noticed with submental reconstruction. Compared with free flaps, submental flap reconstruction was associated with significantly reduced total operative time (mean, 544 vs 683 min; P =. 00817) and duration of hospitalization (4.9 vs 9.8 days; P =. 02067). Submental flaps were significantly less likely to require revision debulking procedures (mean = 0.6) compared with latissimus dorsi flaps (mean, 1.3; P <. 00001) and free flaps (mean, 1.6; P <. 00001). There was 100% flap survival. Conclusion: The musculocutaneous submental flap provides an excellent option for reconstruction of lateral skull base defects given its proximity, reliability, ease of harvest, and exceptional color match. Submental flap reconstruction was associated with reduced operative time, hospitalization duration, and flap revisions.